Influence of Social Media on the Scholastic Development of Students (Trinity Journal of Management, IT & Media (TJMITM), 2018)
Social Media Platforms are the platforms that give  individuals the opportunity to interact, using two  way communication. It means that anyone who has got  an online account can share their opinions with other  social media users. Every other person is now using the Social Media; no  matter what their age or gender is. So, it becomes  extremely important to understand how it influence the  scholastic development and performance of the  students. The young generation is the one that is  caught in the rapid technological advancements and  developments. This study is focussed to find out whether Social Media like  Facebook affects the performance of students  academically. The findings shows that there is no relationship between  social media and scholastic performance as it is  clearly projected in their overall grade average which  doesn't change with the number of hours spent on  social media. Neither does it affect the amount of time  they invest in studying.
Keywords: Social Media; Students; Scholastic performance; Technological advancements